Dust growth, fragmentation, and self-induced dust traps in phantom. Issue 2 (11th August 2021) - Vericel, Arnaud; Gonzalez, Jean-François; Price, Daniel J; Laibe, Guillaume; Pinte, Christophe
ABSTRACT: We present the implementation of a dust growth and fragmentation module in the public smoothed particle hydrodynamics (SPH) code phantom . This module is made available for public use with this paper. The coagulation model considers locally monodisperse dust size distributions around single values that are carried by the SPH particles. Along with the presentation of the model, implementation, and tests, we showcase growth and fragmentation in a few typical circumstellar disc simulations and revisit previous results. The module is also interfaced with the radiative transfer code mcfost, which facilitates the comparison between simulations and ALMA observations by generating synthetic maps. Circumstellar disc simulations with growth and fragmentation reproduce the 'self-induced dust trap' mechanism first proposed in 2017, which supports its existence. Synthetic images of discs featuring this mechanism suggest it would be detectable by ALMA as a bright axisymmetric ring at several tens of au from the star. With this paper, our aim is to provide a public tool to be able to study and explore dust growth in a variety of applications related to planet formation.